Total Synthesis of Crotophorbolone. (22nd October 2015) - Asaba, Taro; Katoh, Yuki; Urabe, Daisuke; Inoue, Masayuki
Abstract: The complex ABC‐tricyclic structure of crotophorbolone, a derivative of the tigliane diterpenoids, was assembled by coupling of simple fragments. The six‐membered C‐ring fragment, having five contiguous stereocenters, was stereoselectively constructed from ( R )‐carvone. After attachment of the five‐membered A‐ring through the π‐allyl Stille coupling reaction, the α‐alkoxy bridgehead radical reaction effected the endo ‐cyclization of the seven‐membered B‐ring by forming the sterically congested bond at C9 and C10 stereospecifically and stereoselectively, respectively. Finally, the functional groups on the 5/7/6‐membered ring system were manipulated by rhodium‐catalyzed C2 olefin isomerization, C13 decarboxylative oxidation, and C4 hydroxylation, thus completing the first total synthesis of crotophorbolone.